174k views
4 votes
I need help with #41 and #42 ASAP please help me.. please show step by step I need to get it done soon because It is due

I need help with #41 and #42 ASAP please help me.. please show step by step I need-example-1
User Thepoetdj
by
4.6k points

1 Answer

5 votes

Answer:

Explanation:

41)


1+2+3+4+...+n=((n+1)*n)/(2) \\\\2+4+6+...+2n=2*(1+2+3+4+...+n)=2*((n+1)*n)/(2) =(n+1)*n\\\\

42)

the square of the sum of the first n natural integers equals the sum of the cubes of these

User Corradolab
by
4.6k points